MANAJEMEN KONFLIK ANTARA PASANGAN SUAMI ISTRI YANG TINGGAL BERSAMA MERTUA DALAM MEWUJUDKAN KELUARGA HARMONIS - Utomo, Arif Budi; Syafaruddin, Muhsan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Marriage is a process of adaptation between two different people to be able to align the same goal in achieving domestic harmony, to be able to minimize a bad thing in navigating it. Conflict is an inevitable phenomenon for a family. A successful partner is a partner who can resolve conflicts appropriately, well and correctly, because the quality of the relationship will be judged by how cleverly the couple manages the conflict. The phenomenon of conflict management in the household will obviously become more complicated and difficult when the couple lives in the house of their in-laws.The purpose of this study is to obtain a conflict management model in couples who live with in-laws, so that it can be known what is the cause of conflict and how to solve conflicts so that they have a harmonious predicate. This research uses a qualitative approach using in-depth interview and observation techniques. The informant participants were 4 (four) married couples who had been selected and met the informant criteria in the study. The results showed that there are differences in conflicts between couples who live with in-laws and those who live independently, so that there are various variations in conflict management in order to create a harmonious family.